Relevance of Accounting Information in Earnings Management to Stock Prices as a Source of Investment Decisions - Yahya, Muhammad Fahri Tsani; Pujiono (Applied Business and Administration Journal, 2025)
This study investigates the influence of earnings management on stock prices within the banking sector companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2023. By employing secondary data from annual financial reports and utilizing statistical analysis through SPSS, the study aims to explore whether accounting information specifically in the form of earnings management plays a significant role in investment decisions. The analysis employs various statistical tests including ANOVA and t-tests to determine the significance of earnings management in influencing stock price movements. The results indicate that earnings management has a significant impact on stock prices, suggesting that it serves as a crucial signal to the market. This study contributes to the literature on accounting information's relevance in investment decisions, offering insights for investors and policymakers in understanding the potential effects of earnings manipulation on financial markets.